Interview‐ and questionnaire‐based surveys on elderly patients' wishes about artificial nutrition and hydration during end‐of‐life care. Issue 11 (13th October 2015) - Yamaguchi, Yasuhiro; Mori, Hiromi; Ishii, Masaki; Okamoto, Sohshi; Yamaguchi, Kiyoshi; Iijima, Setsu; Ogawa, Sumito; Ouchi, Yasuyoshi; Akishita, Masahiro
Abstract : Aim: To promote advance directives, it is crucial to understand how many older persons have wishes related to end‐of‐life care. Additionally, it is important to understand how cognitive function or mood affect these wishes. Methods: For the interview‐based survey, 99 inpatients aged 75 years or older were enrolled after excluding patients with a Mini‐Mental State Examination score of 20 or less. For the questionnaire‐based survey, 99 outpatients aged 75 years or older without dementia were enrolled. Both surveys comprised the same items on older patients' wishes related to artificial nutrition and hydration (ANH) during end‐of‐life care. Results: Of the total enrolled patients, 76.8% participated in the interviews. Of these, 50.0% were against ANH during their end‐of‐life care, including the patients who were definitely against ANH (26.3%). In contrast, just 5.3% wished to receive ANH. In the questionnaire survey, 65.6% of the respondents were against ANH, and 4.9% wished to receive ANH. Aging and Mini‐Mental State Examination scores of less than 24 were significantly associated with a higher tendency to decline from participating in the interview. However, the distribution of the interview answers was not associated with age, Mini‐Mental State Examination or Geriatric Depression Scale scores. Of the interviewed patients, 84.2% agreed to their responses being preserved in their medical records. Conclusions: Although the majority of the elderly patients were against ANH during end‐of‐life care, many patients did not have definite wishes in Japan. The percentage of those who were against ANH was not associated with cognitive function or depressive state.Geriatr Gerontol Int 2016; 16: 1204–1210.